Analysis of The Effect of Community’s Role in CSR Activities on The Image of The Company of Minarak Brantas Gas, Inc. - John Basuki Rahmad; Suwandi Suwandi; Chaidir Kurnia Thoullah Soedaryono; Luthfia Fauzia Dewi Aryanti; Dwi Aprialiasari (ADI Publisher, 2022)
This study aims to determine the effect of Community Perception and Community Participation on the Implementation of Corporate Social Responsibility (CSR) Activities and their impact on Company Image. The independent variables in this study are Community Perception of CSR Activities (X1) and Community Participation in CSR Activities (X2), mediating or intervening variables in this study is the Implementation of Corporate Social Responsibility / CSR (Z) activities, while the dependent variable is Company Image (Y). This type of research is quantitative descriptive research. This research is located in Kalidawir Village and Kedung Banteng Village, Tanggulangin Subdistrict, Sidoarjo Regency. The population in this study is the residents who received CSR program. The sampling technique in this study uses probability sampling techniques with simple random sampling methods. This study uses descriptive analysis and path analysis to determine the results of hypothesis analysis. This study shows the results that there is a significant direct effect of people's perceptions on CSR activities (X1) on the implementation of CSR activities (Z) with the significance of variable X1 of 0.004 (<0.05). The analysis also shows that there is a significant direct effect of community participation in CSR activities (X2) on the implementation of CSR activities (Z) with a significance of variable X2 of 0,000 (<0.05). Other results show that there is a significant direct effect of people's perceptions on CSR activities (X1) on the company's image (Y) with the significance of variable X1 of 0,000 (<0.05); there is a significant direct effect of community participation in CSR activities (X2) on the company's image (Y) with the significance of variable X2 of 0,000 (<0.05); and there is a significant direct effect on the implementation of CSR activities (Z) on the company's image (Y) with the significance of t variable Y of 0,000 (<0.05). The results of testing the indirect effect shows that there is a significant indirect effect of public perception on CSR activities (X1) on corporate image (Y) through the implementation of CSR activities (Z) with the significance of variables X1 on Y through Z of 0.013 (<0.05); and there is a significant indirect effect of community participation in CSR activities (X2) on the company's image (Y) through the implementation of CSR activities (Z) with the significance of the variables X2 on Y through Z of 0,000 (<0.05).